2012
DOI: 10.1111/j.1549-8719.2012.00167.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cerebral Vascular Function by Sirtuin 1

Abstract: Our results support a role for SIRT1 in endothelium-dependent relaxation in the cerebral vasculature and reveal a potential for SIRT1 as a therapeutic target in vascular-related diseases by restoring endothelial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Recent investigations in rodent aortic and human endothelial cells reported the relevance of SIRT1 in eNOS activation; SIRT1 interacts with eNOS, resulting in the activation of the enzyme . In our study, SIRT1 up‐regulation during PC was well correlated with the expression of eNOS which was inhibited after sirtinol or EX527 administration.…”
Section: Discussionsupporting
confidence: 66%
“…Recent investigations in rodent aortic and human endothelial cells reported the relevance of SIRT1 in eNOS activation; SIRT1 interacts with eNOS, resulting in the activation of the enzyme . In our study, SIRT1 up‐regulation during PC was well correlated with the expression of eNOS which was inhibited after sirtinol or EX527 administration.…”
Section: Discussionsupporting
confidence: 66%
“…2011), and others have documented the importance of SIRT-1 expression related to endothelial function in healthy arteries (Mattagajasingh et al . 2007; Tajbakhsh & Sokoya 2012). In an earlier study, we demonstrated that short-term CR could restore arterial SIRT-1 protein concentrations in old mice (Rippe et al .…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia decreases SIRT1 expression in cultured endothelial cells [4], whereas overexpression of SIRT1 prevents the hyperglycemia-induced vascular cell senescence and thereby protects against vascular dysfunction in mice with diabetes [4], [5]. SIRT1 is expressed not only in the endothelium but also in VSMCs [2], [6], [7], where it is required for both growth and proliferation, suggesting a potential role of SIRT1 in the control of vascular function under various stress stimuli.…”
Section: Introductionmentioning
confidence: 99%